Fixed-Time Prescribed Performance Synchronization for Complex Networks via Aperiodically Intermittent Event-Triggered Pinning Control - Junru Zhang; Jian-An Wang; Jie Zhang; Mingjie Li (IEEE Access)
This paper deals with the fixed-time prescribed performance synchronization of complex networks using intermittent event-triggered pinning control. A fixed-time prescribed performance function is employed to guarantee the specified steady and transient performance of synchronization error. Different from classical controllers with fixed sets of pinning nodes, an appropriate event-triggered aperiodic intermittent pinning controller (ETAIPC) is designed via the average control rate. Several necessary conditions are derived to ensure the fixed-time synchronization. A convenient algorithm is adopted to renew pinning set. The Zeno behavior is also excluded through a rigorous analysis. The theoretical results are applied to Chua’s circuit system, and numerical simulation are made to show the feasibility of the proposed methods.